Social Support During Incarceration: Predictors of External Social Support for Incarcerated Individuals - Kjellstrand, Jean M. (American journal of criminal justice, 2023)
When individuals reenter their communities after incarceration, they frequently have difficulties in meeting their basic needs. Social support can help buffer some of the challenges reentering individuals face. Research has demonstrated that reentering individuals with close social bonds are more likely to secure employment, experience better mental health, exhibit lower levels of hostility, desist from criminal activity, and avoid recidivating. Although social support is helpful during reentry, incarceration often erodes external social support networks. While research points to the importance of sustaining or building external support during and after incarceration, information is limited regarding what factors may influence social support networks of correction involved individuals. The current study seeks to understand what factors impact the external social support received by individuals while they are in prison. Using structural equation modeling, the study examines the impact of key demographic characteristics, past childhood adversity, mental health diagnoses, and substance misuse on external support individuals receive during incarceration. Participants in the study included 413 adults who were recently released from the Oregon State prison system and were participating in a transitional housing program. Controlling for other covariates, having a mental health diagnosis, having experienced childhood adversity, and being male all predicted lower levels of external social support during incarceration. These may be key populations to target to help bolster their external social support networks prior to their release from prison. Suggestions are made for future research and intervention development.